Electrolyte and lithium ion battery

By optimizing the ratio of additives and solvents in the electrolyte, the stability of the solid electrolyte interface film in lithium-ion batteries is improved, the problem of SEI film is solved, the performance and consistency of the battery is improved, and it is suitable for industrial production.

CN119230952APending Publication Date: 2024-12-31HUNAN SHINZOOM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411643361.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Existing electrolytes lead to inhomogeneity and structural instability of solid electrolyte interface films (SEI films) in lithium-ion batteries, affecting the electrochemical performance of the battery and reducing the battery capacity, survival rate and consistency.

Method used

Using an electrolyte, its mass percentage includes ≥13 wt% additive, ≤72 wt% solvent and residual metal salt. By optimizing the composition and proportion of additives and solvents, the stability and ionic conductivity of the electrolyte are improved. Reduced contact between solvent and electrode.

Benefits of technology

Improves battery capacity, first-time Coulomb efficiency, survival rate and consistency, and is suitable for industrial production of batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005139073370000141
    Figure BDA0005139073370000141
  • Figure BDA0005139073370000151
    Figure BDA0005139073370000151
Patent Text Reader

Abstract

The invention relates to an electrolyte and a lithium ion battery, the electrolyte comprises more than or equal to 13wt% of an additive, less than or equal to 72wt% of a solvent and the balance of metal salt based on the mass percentage of the electrolyte being 100wt%; the additive comprises any one or a combination of at least two of fluoroethylene carbonate, 1, 3-propane sultone, ethylene carbonate, vinylethylene carbonate or lithium bis (oxalato) borate. According to the electrolyte provided by the invention, the ratio of the additive to the metal salt is increased, the use amount of the solvent is properly reduced, and the contact between solvent molecules and an electrode is reduced, so that the stability of the electrolyte is improved; by using the electrolyte provided by the invention, the capacity and the first coulombic efficiency of the battery are improved, the survival rate, the qualification rate and the consistency of the battery can also be improved, and industrial production of the battery is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries and relates to a battery material, in particular to an electrolyte and a lithium ion battery. Background Art

[0002] With the rapid development of modern science and technology, batteries, as an important energy storage device, play an irreplaceable role in many fields. In various battery systems, electrolyte is a key component, and its performance directly affects the overall performance and service life of the battery.

[0003] During the charge and discharge process of the battery, a solid electrolyte interface film (SEI film) will be formed on the electrode surface. A high-quality SEI film has good stability and ion conductivity, which can effectively prevent further reactions between the electrolyte and the electrode, and protect the electrode material from corrosion while ensuring the smooth embedding and removal of ions on the electrode surface. The composition of the electrolyte affects the growth mechanism and chemical composition of the SEI film. If the thickness of the SEI film is uneven, the structure is unstable, or the ion conductivity is poor, the electrochemical performance of the battery will be reduced.

[0004] Therefore, providing an electrolyte and a lithium-ion battery to optimize the composition of the electrolyte and improve the performance of the battery is of great significance to the development of the battery industry. Summary of the invention

[0005] The object of the present invention is to provide an electrolyte and a lithium ion battery, wherein the electrolyte has good stability; a battery using the electrolyte can not only increase the capacity and the first coulombic efficiency, but also improve the survival rate, the qualified rate and the consistency of the battery, which is beneficial to industrial production.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides an electrolyte, wherein, based on the mass percentage of the electrolyte being 100 wt %, the electrolyte comprises ≥ 13 wt % of an additive, ≤ 72 wt % of a solvent, and the remainder being a metal salt.

[0008] The additive includes any one of fluoroethylene carbonate (FEC), 1,3-propane sultone (PS), vinylene carbonate (VC), vinyl ethylene carbonate (VEC) or lithium bis(oxalatoborate) (LiBOB) or a combination of at least two thereof.

[0009] Preferably, the electrolyte comprises, by mass percentage, 13 wt % to 18 wt % of additives, 67 wt % to 70 wt % of solvents, and 12 wt % to 18 wt % of metal salts.

[0010] Preferably, the solvent comprises ethyl methyl carbonate (EMC) and / or ethylene carbonate (EC).

[0011] Preferably, the solvent comprises a combination of ethyl methyl carbonate and ethylene carbonate.

[0012] Preferably, the mass ratio of the ethyl methyl carbonate to ethylene carbonate is 1:1 to 4:1.

[0013] Preferably, the additive comprises a combination of fluoroethylene carbonate, 1,3-propane sultone and vinyl ethylene carbonate.

[0014] Preferably, in terms of mass percentage, the electrolyte comprises ethylene carbonate in an amount of 1 wt % to 5 wt %.

[0015] Preferably, the additive further comprises lithium bis(oxalatoborate) (LiBOB).

[0016] In terms of mass percentage, the mass percentage of lithium bis(oxalatoborate) in the electrolyte is 0.5wt% to 2wt%.

[0017] Preferably, the metal salt is a lithium salt.

[0018] Preferably, the lithium salt includes any one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4) or lithium hexafluoroarsenate (LiAsF6) or a combination of at least two thereof.

[0019] In a second aspect, the present invention provides a lithium ion battery, wherein the lithium ion battery comprises the electrolyte described in the first aspect.

[0020] Preferably, the lithium-ion battery comprises a positive electrode, a negative electrode and an electrolyte. The negative electrode comprises a negative electrode current collector and a negative electrode active material disposed on the negative electrode current collector.

[0021] Preferably, the negative electrode active material of the lithium ion battery comprises a graphite negative electrode material.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The electrolyte provided by the present invention increases the proportion of additives and metal salts, and appropriately reduces the amount of solvent used, reducing the contact between solvent molecules and electrodes, thereby improving the stability of the electrolyte; the use of the electrolyte provided by the present invention increases the capacity and first coulomb efficiency of the battery, and can also improve the survival rate, pass rate and consistency of the battery, which is beneficial to the industrial production of the battery. DETAILED DESCRIPTION

[0024] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0025] [Electrolyte]

[0026] In a first aspect, the present application provides an electrolyte, which comprises ≥13wt% of additives, ≤72wt% of solvents, and the remainder of metal salts, based on the mass percentage of the electrolyte being 100wt%.

[0027] The additive includes any one of fluoroethylene carbonate (FEC), 1,3-propane sultone (PS), vinylene carbonate (VC), vinyl ethylene carbonate (VEC) or lithium bis(oxalatoborate) (LiBOB) or a combination of at least two thereof. Typical but non-limiting combinations include a combination of FEC and PS, a combination of PS and VC, a combination of VC and VEC, a combination of FEC, PS, VC, a combination of VC, VEC and LiBOB, or a combination of FEC, PS, VC, VEC and LiBOB.

[0028] The main function of the electrolyte includes providing a transmission medium for ions. In order to ensure the activity space and migration efficiency of the ions, it is generally necessary to ensure a sufficient amount of solvent in the electrolyte. The electrolyte provided by the present invention greatly increases the amount of additives, while the amount of solvent is relatively reduced. By coordinating the amount of additives and solvents in the electrolyte, not only the performance of the electrolyte is guaranteed, but also the contact between the solvent molecules and the electrodes can be reduced, thereby improving the stability of the electrolyte.

[0029] In the electrolyte provided by the present invention, the mass percentage of the additive is ≥13wt%, for example, it can be 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 20wt% or 22wt%, but is not limited to the listed values, and the remaining unlisted values ​​within the numerical range are also applicable.

[0030] The use of additives in the electrolyte can improve the ionic conductivity of the electrolyte, reduce internal resistance, and improve rate performance. Within a certain range, as the amount of additives in the electrolyte increases, the viscosity of the electrolyte will gradually increase, but the proportion of anions and cations in the corresponding solvent will be improved, and the ionic conductivity will also increase accordingly. Therefore, as a preferred technical solution to ensure the performance of the electrolyte and reduce the amount of solvent, the mass percentage of the additive in the electrolyte is 13wt% to 18wt%.

[0031] In the electrolyte provided by the present invention, the amount of solvent used is ≤72wt%, for example, it can be 65wt%, 66wt%, 68wt%, 70wt%, 71wt% or 72wt%, but is not limited to the listed values, and the remaining unlisted values ​​within the numerical range are also applicable.

[0032] The present invention reduces the contact between solvent molecules and electrodes and improves the stability of the electrolyte by reducing the mass percentage of the solvent in the electrolyte to ≤72wt%, but in order to ensure the activity space and migration efficiency of the ions, it is generally necessary to ensure sufficient solvent usage in the electrolyte. As a preferred technical solution of the present invention, the amount of solvent in the electrolyte is 67wt% to 70wt%.

[0033] In some embodiments, the electrolyte includes, in percentage by mass, 13wt% to 18wt% of an additive, 67wt% to 70wt% of a solvent, and 12wt% to 18wt% of a metal salt, wherein the mass percentage of the metal salt is 12wt% to 18wt%, for example, 12wt%, 14wt%, 15wt%, 16wt% or 18wt%, but is not limited to the listed values, and the remaining unlisted values ​​within the numerical range are equally applicable.

[0034] In certain embodiments, the solvent includes ethyl methyl carbonate (EMC) and / or ethylene carbonate (EC).

[0035] In certain embodiments, the solvent is a combination of ethyl methyl carbonate and ethylene carbonate.

[0036] In certain embodiments, the mass ratio of ethyl methyl carbonate to ethylene carbonate is 1:1 to 4:1, for example, 1:1, 6:4, 7:3 or 8:2, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] Appropriate additive ingredients are conducive to obtaining high-quality SEI films, which can effectively prevent further reactions between the electrolyte and the electrode, while protecting the electrode material from corrosion and ensuring the smooth embedding and extraction of ions on the electrode surface.

[0038] In certain embodiments, the additive includes a combination of fluoroethylene carbonate, 1,3-propane sultone, and vinyl ethylene carbonate.

[0039] In some embodiments, the electrolyte includes vinyl ethylene carbonate in an amount of 1 wt% to 5 wt% by mass, for example, 1 wt%, 2 wt%, 3 wt%, 4 wt% or 5 wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0040] In certain embodiments, the additive includes a combination of fluoroethylene carbonate, 1,3-propane sultone, vinyl ethylene carbonate, and lithium bis(oxalatoborate).

[0041] In some embodiments, the mass percentage of lithium dioxalatoborate in the electrolyte is 0.5wt% to 2wt%, for example, 0.5wt%, 1wt%, 1.5wt% or 2wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0042] In certain embodiments, the metal salt is a lithium salt.

[0043] In certain embodiments, the lithium salt includes any one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4) or lithium hexafluoroarsenate (LiAsF6) or a combination of at least two thereof, typical non-limiting combinations include a combination of LiPF6 and LiBF4, a combination of LiBF4 and LiClO4, a combination of LiClO4 and LiAsF6, a combination of LiPF6, LiBF4 and LiClO4, or a combination of LiPF6, LiBF4, LiClO4 and LiAsF6.

[0044] In certain embodiments, the method for preparing the electrolyte of the present invention comprises the following steps: uniformly mixing additives, solvents and metal salts according to the formula amounts.

[0045] In some embodiments, the preparation method of the electrolyte includes: mixing a solvent and a metal salt, dissolving them, and then mixing an additive to prepare an electrolyte. Based on the total mass percentage of the solvent, the metal salt and the additive as 100wt%, the electrolyte includes 13wt% to 18wt% of the additive, 67wt% to 70wt% of the solvent and 12wt% to 18wt% of the metal salt.

[0046] [Lithium-ion battery]

[0047] Generally, lithium-ion batteries include a positive electrode, a negative electrode, a separator, and an electrolyte. During the charge and discharge process of a lithium-ion battery, lithium ions are inserted and removed back and forth between the positive electrode and the negative electrode. The separator is set between the positive electrode and the negative electrode to prevent the positive and negative electrodes from short-circuiting, while allowing active ions to pass through. The electrolyte plays a role in conducting active ions between the positive electrode plate and the negative electrode plate.

[0048] The lithium-ion battery provided in the embodiments of the present application includes the electrolyte of the first aspect of the present application.

[0049] In some embodiments, the positive electrode of the lithium-ion battery includes a positive electrode current collector and a positive electrode film layer located on at least one side of the positive electrode current collector, and the positive electrode film layer includes a positive electrode active material. The positive electrode active material may include a lithium sheet or a lithium-containing transition metal oxide.

[0050] Optionally, the lithium-containing transition metal oxide includes lithium iron phosphate or a nickel-cobalt-manganese ternary material, and the nickel-cobalt-manganese ternary material may include one or more of lithium nickel-cobalt-manganese oxide and its modified compounds. The modified compound of lithium nickel-cobalt-manganese oxide may include materials well known in the art, for example, may include lithium nickel-cobalt-manganese oxide that has been modified by doping or surface modification.

[0051] In some embodiments, the compaction density of the positive electrode film layer can be 3.0 g / cm 3 Up to 3.8g / cm 3 , optional 2.9g / cm 3 Up to 3.6g / cm 3 .

[0052] The compaction density of the positive electrode film layer has a meaning well known in the art, and can be tested using equipment and methods known in the art. The compaction density of the positive electrode film layer = the surface density of the positive electrode film layer / the thickness of the single-sided positive electrode film layer. The surface density of the positive electrode film layer has a meaning well known in the art, and can be tested using equipment and methods known in the art, such as taking a single-sided coated and cold-pressed positive electrode pole piece (if it is a double-sided coated positive electrode pole piece, the positive electrode film layer on one side can be wiped off first), punching it into small discs, and weighing it; then wipe off the positive electrode film layer of the weighed positive electrode pole piece, and weigh the weight of the current collector. The surface density of the positive electrode film layer = (weight of the small disc - weight of the current collector) / area of ​​the small disc.

[0053] In some embodiments, the positive electrode film layer may further include a positive electrode conductive agent. The present application has no particular restrictions on the type of the positive electrode conductive agent. As an example, the positive electrode conductive agent includes at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0054] In some embodiments, the positive electrode film layer may further include a positive electrode binder. The present application has no particular restrictions on the type of the positive electrode binder. As an example, the positive electrode binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylic resin.

[0055] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0056] The positive electrode film layer is usually formed by coating the positive electrode slurry on the positive electrode current collector, drying and cold pressing. The positive electrode slurry is usually formed by dispersing the positive electrode active material, optional conductive agent, optional binder and any other components in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP), but is not limited thereto.

[0057] In certain embodiments, lithium metal may be used to replace the positive electrode of a lithium-ion battery.

[0058] In certain embodiments, in the lithium-ion battery of the embodiments of the present application, the negative electrode may include a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector and including a negative electrode active material. For example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0059] The negative electrode active material may adopt the negative electrode active material for secondary batteries known in the art. As an example, the negative electrode active material may include but is not limited to at least one of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate. The silicon-based material may include at least one of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite and silicon alloy material. The tin-based material may include at least one of elemental tin, tin oxide and tin alloy material.

[0060] In certain embodiments, the negative electrode active material is a graphite negative electrode material not coated with amorphous carbon.

[0061] In some embodiments, the negative electrode film layer may further include a negative electrode conductive agent. The present application has no particular restrictions on the type of the negative electrode conductive agent. As an example, the negative electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0062] In some embodiments, the negative electrode film layer may further include a negative electrode binder. The present application has no particular restrictions on the type of the negative electrode binder. As an example, the negative electrode binder may include at least one of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, aqueous acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS).

[0063] In some embodiments, the negative electrode film layer may further include other additives, such as, for example, thickeners, such as sodium carboxymethyl cellulose (CMC), PTC thermistor materials, and the like.

[0064] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0065] The negative electrode film layer is usually formed by coating the negative electrode slurry on the negative electrode current collector, drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, optional conductive agent, optional binder, and other optional auxiliary agents in a solvent and stirring them evenly. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited thereto.

[0066] The negative electrode plate does not exclude other additional functional layers besides the negative electrode film layer. For example, in some embodiments, the negative electrode plate also includes a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector. In some embodiments, the negative electrode plate of the present application also includes a protective layer covering the surface of the negative electrode film layer.

[0067] The embodiments of the present application have no particular restrictions on the type of separator used in the electrode assembly of the battery cell, and any known porous structure separator with good chemical stability and mechanical stability can be selected.

[0068] In some embodiments, the material of the isolation membrane may include at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film. When the isolation membrane is a multi-layer composite film, the materials of each layer are the same or different.

[0069] In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be made into a lithium-ion battery.

[0070] In some embodiments, the outer packaging of the lithium-ion battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS).

[0071] Example

[0072] Example 1

[0073] Preparation of negative electrode

[0074] The graphite negative electrode material (artificial graphite), conductive agent Super P and binder PVDF were mixed with solvent NMP in a mass ratio of 91.6:6.6:1.8 to prepare a uniform slurry with a solid content of 50%; after coating on the current collector copper foil, it was dried and rolled to make the surface density of 1.3 mg / cm 2 ; Then cut into circular pole pieces with a diameter of 14 mm, vacuum dry at a temperature of 80°C for 6 hours to prepare the negative pole piece.

[0075] Preparation of electrolyte

[0076] Ethyl methyl carbonate (EMC) and ethylene carbonate (EC) were mixed uniformly at a volume ratio of 8:2, and then solid lithium hexafluorophosphate (LiPF6) was added thereto as a lithium salt to dissolve the mixture. At this time, the content of lithium hexafluorophosphate was 1.2 mol / L.

[0077] Fluoroethylene carbonate (FEC), 1,3-propane sultone (PS) and vinyl ethylene carbonate (VEC) were added respectively to prepare the electrolyte of Example 1, and the mass ratio of FEC, PS and VEC was 10:3:5 (the electrolyte included 18.0wt% of additives, 69.4wt% of solvents and 12.6wt% of lithium hexafluorophosphate).

[0078] Preparation of coin cells for experiments

[0079] A lithium sheet with a thickness of 1 mm and a diameter of 16 mm was used as the counter electrode of the half-cell to provide a lithium source. The negative electrode sheet obtained by the above method was then placed opposite to the lithium sheet via a separator (polyethylene film). After the electrolyte obtained by the above method was injected, an experimental lithium-ion secondary battery (2430 button cell) was prepared.

[0080] Gram capacity and first coulombic efficiency determination

[0081] The prepared button cell was tested using a constant current charge and discharge mode, with the discharge rate set to 0.05C, the charge rate set to 0.1C, the discharge cut-off voltage set to 5mV, and the charge cut-off voltage set to 2V, to obtain the reversible gram capacity and the first coulomb efficiency. The first coulomb efficiency = first charge gram capacity / first discharge gram capacity × 100%.

[0082] Determination of battery survival rate, pass rate and consistency

[0083] After the first charge and discharge of 10 button batteries with the discharge rate set to 0.05C, the charge rate set to 0.1C, the discharge cut-off voltage set to 5mV, and the charge cut-off voltage set to 2V, the survival rate, pass rate and consistency were measured.

[0084] The survival rate is the percentage of button cells remaining in the total number of button cells after excluding those with obvious short circuits, overcharge or over-discharge. Overcharge or over-discharge means that any of the actual charging or discharging data exceeds 20% of the nominal gram capacity.

[0085] The qualified rate is the percentage of button batteries with STD (relative standard deviation) of charged gram capacity less than 0.4%, STD (relative standard deviation) of first coulomb efficiency less than 0.4% and first coulomb efficiency range less than 1% to the total number of button batteries.

[0086] The consistency is judged by the STD (relative standard deviation) of the gram capacity and the first coulomb efficiency data obtained by the first charge and discharge. The smaller the STD, the better the consistency of the batch of batteries; (STD < 0.9 is considered to be good consistency, otherwise it is poor).

[0087] Example 2

[0088] This example prepared an electrolyte in the same manner as in Example 1, except that the composition of the additives was different from that in Example 1, and the rest was the same as in Example 1. In addition, a lithium ion battery of Example 2 was manufactured in the same manner as in Example 1. For the obtained battery, the battery characteristics were evaluated in the same manner as in Example 1.

[0089] In this embodiment, fluoroethylene carbonate (FEC), 3-propane sultone (PS), vinyl ethylene carbonate (VEC) and lithium borate oxalate (LiBOB) were added as additives, and the mass ratio of FEC, PS, VEC and LiBOB was 10:3:1:1 to prepare the electrolyte of Example 2 (the electrolyte included 15.0wt% of additives, 69.8wt% of solvent and 15.2wt% of lithium hexafluorophosphate).

[0090] Example 3

[0091] This example prepared an electrolyte in the same manner as in Example 1, except that the composition of the additives was different from that in Example 1, and the rest was the same as in Example 1. In addition, a lithium ion battery of Example 3 was manufactured in the same manner as in Example 1. For the obtained battery, the battery characteristics were evaluated in the same manner as in Example 1.

[0092] In this embodiment, fluoroethylene carbonate (FEC), 3-propane sultone (PS), vinylene carbonate (VC) and lithium borate oxalate (LiBOB) were added as additives, and the mass ratio of FEC, PS, VC and LiBOB was 10:3:1:1 to prepare the electrolyte of Example 3 (the electrolyte included 15.0wt% of additives, 69.8wt% of solvent and 15.2wt% of lithium hexafluorophosphate).

[0093] Example 4

[0094] This example prepared an electrolyte in the same manner as in Example 1, except that the composition of the additives and the solvent of the electrolyte were different from those in Example 1, and the rest was the same as in Example 1. In addition, a lithium ion battery of Example 4 was manufactured in the same manner as in Example 1. For the obtained battery, the battery characteristics were evaluated in the same manner as in Example 1.

[0095] In this embodiment, fluoroethylene carbonate (FEC) and 3-propane sultone (PS) were added as additives, and the mass ratio of FEC to PS was 10:3 to prepare the electrolyte of Example 4 (the electrolyte included 13.0 wt% of additives, 69.0 wt% of solvent and 18.0 wt% of lithium hexafluorophosphate).

[0096] Example 5

[0097] This example prepared an electrolyte in the same manner as in Example 1, except that the composition of the additives and the solvent of the electrolyte were different from those in Example 1, and the rest was the same as in Example 1. In addition, a lithium ion battery of Example 5 was manufactured in the same manner as in Example 1. For the obtained battery, the battery characteristics were evaluated in the same manner as in Example 1.

[0098] In this embodiment, fluoroethylene carbonate (FEC), 3-propane sultone (PS), and vinyl ethylene carbonate (VEC) were added as additives, and the mass ratio of FEC, PS, and VEC was 10:3:5 to prepare the electrolyte of Example 6 (the electrolyte included 18.0wt% of additives, 69.4wt% of solvent and 12.6wt% of lithium hexafluorophosphate; the solvent was ethyl methyl carbonate and vinyl carbonate in a mass ratio of 1:1).

[0099] Comparative Example 1

[0100] In this comparative example, the electrolyte was prepared in the same manner as in Example 1, and the proportions of the additive, solvent, and lithium salt in the electrolyte were adjusted, and the rest were the same as in Example 1. In addition, the lithium ion battery of Comparative Example 1 was manufactured in the same manner as in Example 1. For the obtained battery, the battery characteristics were evaluated in the same manner as in Example 1.

[0101] In this comparative example, ethyl methyl carbonate (EMC) and ethylene carbonate (EC) were uniformly mixed in a volume ratio of 1:1, and then solid lithium hexafluorophosphate (LiPF6) as a lithium salt was added thereto for dissolution. At this time, the content of lithium hexafluorophosphate was 0.8 mol / L.

[0102] In this comparative example, fluoroethylene carbonate (FEC), 3-propane sultone (PS) and vinyl ethylene carbonate (VEC) were added as additives, and the mass ratio of FEC, PS and VEC was 7:3:1 to prepare the electrolyte of comparative example 1 (the electrolyte included 11.0wt% of additives, 79.0wt% of solvent and 10.0wt% of lithium hexafluorophosphate).

[0103] Comparative Example 2

[0104] In this comparative example, the electrolyte was prepared in the same manner as in Example 1, and the proportions of the additive, solvent, and lithium salt in the electrolyte were adjusted, and the rest were the same as in Example 1. In addition, the lithium ion battery of Comparative Example 2 was manufactured in the same manner as in Example 1. For the obtained battery, the battery characteristics were evaluated in the same manner as in Example 1.

[0105] In this comparative example, ethyl methyl carbonate (EMC) and ethylene carbonate (EC) were uniformly mixed in a volume ratio of 8:2, and then solid lithium hexafluorophosphate (LiPF6) as a lithium salt was added thereto for dissolution. At this time, the content of lithium hexafluorophosphate was 0.6 mol / L.

[0106] In this comparative example, fluoroethylene carbonate (FEC), 3-propane sultone (PS), and vinyl ethylene carbonate (VC) were added as additives, and the mass ratio of FEC, PS, and VC was 10:3:1 to prepare the electrolyte of comparative example 3 (the electrolyte included 14.0wt% of additives, 78.0wt% of solvent, and 8.0wt% of lithium hexafluorophosphate).

[0107] Comparative Example 3

[0108] In this comparative example, the electrolyte was prepared in the same manner as in Example 1, and the proportions of the additive, solvent, and lithium salt in the electrolyte were adjusted, and the rest were the same as in Example 1. In addition, the lithium ion battery of Comparative Example 3 was manufactured in the same manner as in Example 1. For the obtained battery, the battery characteristics were evaluated in the same manner as in Example 1.

[0109] In this comparative example, ethyl methyl carbonate (EMC) and ethylene carbonate (EC) were uniformly mixed in a volume ratio of 8:2, and then solid lithium hexafluorophosphate (LiPF6) as a lithium salt was added thereto for dissolution. At this time, the content of lithium hexafluorophosphate was 0.6 mol / L.

[0110] In this comparative example, fluoroethylene carbonate (FEC), 3-propane sultone (PS), and vinyl ethylene carbonate (VEC) were added as additives, and the mass ratio of FEC, PS, and VEC was 10:4:5 to prepare the electrolyte of comparative example 3 (the electrolyte included 19.0wt% of additives, 73.0wt% of solvent, and 8.0wt% of lithium hexafluorophosphate).

[0111] Table 1

[0112]

[0113]

[0114] In summary, the electrolyte provided by the present invention increases the proportion of additives and metal salts, and appropriately reduces the amount of solvent used, reduces the contact between solvent molecules and electrodes, and thus improves the stability of the electrolyte; the use of the electrolyte provided by the present invention increases the capacity and first coulomb efficiency of the battery, and can also improve the survival rate, pass rate and consistency of the battery, which is beneficial to the industrial production of the battery.

[0115] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. An electrolyte, characterized in that: Based on the mass percentage of the electrolyte being 100wt%, the electrolyte comprises ≥13wt% of additives, ≤72wt% of solvent and the remainder of metal salt; The additive includes any one of fluoroethylene carbonate, 1,3-propane sultone, vinylene carbonate, vinylethylene carbonate or lithium bis(oxalatoborate), or a combination of at least two thereof.

2. The electrolyte according to claim 1, characterized in that In terms of mass percentage, the electrolyte includes 13 wt % to 18 wt % of additives, 67 wt % to 70 wt % of solvents, and 12 wt % to 18 wt % of metal salts.

3. The electrolyte according to claim 1, characterized in that The solvent includes ethyl methyl carbonate and / or ethylene carbonate.

4. The electrolyte according to claim 3, characterized in that The solvent comprises a combination of ethyl methyl carbonate and ethylene carbonate; And / or, the mass ratio of ethyl methyl carbonate to ethylene carbonate is 1:1 to 4:

1.

5. The electrolyte according to claim 1, characterized in that The additive includes a combination of fluoroethylene carbonate, 1,3-propane sultone and vinyl ethylene carbonate.

6. The electrolyte according to claim 5, characterized in that In terms of mass percentage, the electrolyte includes ethylene carbonate in an amount of 1 wt % to 5 wt %.

7. The electrolyte according to any one of claim 5, characterized in that The additive also includes lithium bis(oxalatoborate); In terms of mass percentage, the mass percentage of lithium bis(oxalatoborate) in the electrolyte is 0.5wt% to 2wt%.

8. The electrolyte according to claim 1, characterized in that The metal salt is a lithium salt; And / or, the lithium salt includes any one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate or lithium hexafluoroarsenate, or a combination of at least two thereof.

9. A lithium ion battery, characterized in that: The lithium-ion battery comprises the electrolyte according to any one of claims 1 to 8.

10. The lithium ion battery according to claim 9, characterized in that: The negative electrode active material of the lithium ion battery includes a graphite negative electrode material.